Mental health literacy and young people - Crawford, Paul (Emerald points., 2022)
In the wake of Covid-19, and the onslaught of major war breaking out once again in Europe, the mental health of young people is at stake, with increasing numbers struggling with anxiety, depression, loneliness and other psychological challenges. Key reports highlight a mental health emergency among young people with significant gaps in service provision. It is time to take seriously a need for enhanced mental health literacy among this population. It is also time to be more creative about how best to achieve this upstream and downstream of mental disorders. Drawing on the hugely successful campaign with Aardman Animations called What's Up With Everyone? Paul Crawford provides an accessible, lively and creative entry point to mental health literacy and young people at a time of unprecedented challenges. It invites young people to play a more active role in advancing their own mental health, not least through fuller use of social and creative assets.